2017
DOI: 10.1107/s1600577516018452
|View full text |Cite
|
Sign up to set email alerts
|

Uridine as a new scavenger for synchrotron-based structural biology techniques

Abstract: Macromolecular crystallography (MX) and small-angle X-ray scattering (SAXS) studies on proteins at synchrotron light sources are commonly limited by the structural damage produced by the intense X-ray beam. Several effects, such as aggregation in protein solutions and global and site-specific damage in crystals, reduce the data quality or even introduce artefacts that can result in a biologically misguiding structure. One strategy to reduce these negative effects is the inclusion of an additive in the buffer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“… summarize all the results on scavengers for MX up to 2013, and to the authors knowledge, there have been no additional studies since then apart from that of Ref. on uridine as a radical scavenger for both MX and SAXS.…”
Section: Introductionmentioning
confidence: 97%
“… summarize all the results on scavengers for MX up to 2013, and to the authors knowledge, there have been no additional studies since then apart from that of Ref. on uridine as a radical scavenger for both MX and SAXS.…”
Section: Introductionmentioning
confidence: 97%
“…The limiting factor in microcrystallography is that the total usable diffraction from each crystal is limited by the dose limit that can be tolerated by the crystal (Owen et al, 2006). Although laboratory techniques exist to slightly improve the dose tolerance (see, for example, Crosas et al, 2017;Allan et al, 2013), serial crystallography from microcrystals is usually the method of choice for overcoming the dose limit of small crystals.…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal paper, Blake and Phillips observed that the structure factors of some reflections from myoglobin crystals increased, while others decreased, leading them to suggest that specific structural damage to certain amino acids must be occurring (Blake & Philips, 1962), a hypothesis confirmed later for RT crystals (Helliwell, 1988). The occurrence of specific damage at RT remains controversial, however, with some reports showing evidence for disulfide damage (Southworth-Davies et al, 2007;Coquelle et al, 2015), while others do not (Roedig et al, 2016), including Crosas et al in this issue (Crosas et al, 2017). Despite increased radiation sensitivity, RT data collection is desirable because the modification of conformational heterogeneity within the crystalline protein that may occur during cryocooling is avoided, potentially providing physiologically more meaningful structures (Fraser et al, 2011).…”
Section: Radiation Damagementioning
confidence: 98%
“…In the literature to date, there are conflicting results on the efficacy of the same compounds, and no consensus has yet emerged as to their effectiveness. Tests of uridine, a previously untried scavenger, for synchrotron-based structural biology techniques (MX and SAXS) are reported in this issue (Crosas et al, 2017). At 1 M concentration, uridine was found to be effective in increasing the dose-to-half-intensity, D 1/2 , by a factor of 1.7 for RT MX data collection on chicken egg-white lysozyme crystals, but was found to be ineffective at cryotemperatures (100 K).…”
Section: Radiation Damagementioning
confidence: 99%
See 1 more Smart Citation